2009
DOI: 10.1097/mop.0b013e32832db986
|View full text |Cite
|
Sign up to set email alerts
|

An update on alopecia areata

Abstract: Although multiple potential susceptibility loci have been implicated, the genetics of alopecia areata is still unclear. The role of any potential environmental contributors is also unclear. Quality evidence for efficacy of currently used treatments for alopecia areata is lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 49 publications
1
35
0
4
Order By: Relevance
“…A phase II, placebo-controlled trial of efalizumab treatment showed no statistically significant effect on hair regrowth, quality-of-life, or changes in biologic markers of disease severity in patients with alopecia areata. 2 Development of alopecia areata during biological therapy of psoriasis shows features of a "biological drug-induced Renbök phenomenon". The Renbök phenomenon or inverse Köbner phenomenon refers to normal hair growth in psoriatic lesions observed in patients with coexisting psoriasis and alopecia areata.…”
Section: Figure 1 Hair Loss In the Patient Treated With Ustekinumab (mentioning
confidence: 99%
See 1 more Smart Citation
“…A phase II, placebo-controlled trial of efalizumab treatment showed no statistically significant effect on hair regrowth, quality-of-life, or changes in biologic markers of disease severity in patients with alopecia areata. 2 Development of alopecia areata during biological therapy of psoriasis shows features of a "biological drug-induced Renbök phenomenon". The Renbök phenomenon or inverse Köbner phenomenon refers to normal hair growth in psoriatic lesions observed in patients with coexisting psoriasis and alopecia areata.…”
Section: Figure 1 Hair Loss In the Patient Treated With Ustekinumab (mentioning
confidence: 99%
“…1 In both diseases an autoimmune process is the likely pathogenic mechanism, and both show at least partial response to classical immunosuppressive therapy. 2,3 Attempts to treat alopecia areata with biological, immunosuppressive, anti-psoriasis drugs, which target specific molecules, such as tumor necrosis alpha (adalimumab, etanercept, infliximab), CD2 (alefacept) or CD11a (efalizumab) were unsuccessful. 4 This may lead to the in indirect conclusion that these molecules do not play a key role in alopecia areata.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] İnfantil dönemde görülen alopesi nedenlerinin ayırıcı tanısına giren hastalıklar Tablo 1'de görülmektedir. [1][2][3][5][6][7][8][9][10][12][13][14][15][16] Bu olguda SHA hayatın 6. ayından sonra tedricen gelişmiş idi, ancak SHA'lı birçok hastada alopesinin doğumda ya da doğumdan hemen sonra başladığı bildirilmiştir. Bu olguda hayatın genellikle ilk 3 ayında görülen SHA'nın ilk aylarda aile tarafından fark edilememiş olması da dikkat çeki-cidir.…”
Section: Discussionunclassified
“…Alopesi areata (AA) insidansı yılda 20,2/100,000 olan, saç, sakal gibi vücudun kıllı bölgelerini etkileyen otoimmün bir hastalıktır [1][2][3] . Alopesi areatanın patogenezi tam olarak bilinmemekte ise de günümüzdeki baskın görüş, genetik yatkınlığı olan bireylerde, çevresel tetikleyicilerle kıl foliküllerine karşı gelişen organ spesifik otoimmün bir hastalık olduğu yönündedir 1,2 .…”
Section: Introductionunclassified
“…Alopesi areatanın patogenezi tam olarak bilinmemekte ise de günümüzdeki baskın görüş, genetik yatkınlığı olan bireylerde, çevresel tetikleyicilerle kıl foliküllerine karşı gelişen organ spesifik otoimmün bir hastalık olduğu yönündedir 1,2 . Bu çalışmada polikliniğimize başvuran AA'lı hastaların, klinik ve demografik özellikleri ile hastalık seyrindeki kötü prognostik faktörleri incelenerek, AA'nın Türkiye'deki epidemiyolojik özelliklerinin tanınmasına katkı amaçlandı 1,4,5 .…”
Section: Introductionunclassified